Study on Stress-Strain effect of reinforced Metakaolin based GPC under compression. (2020) - Parthiban, D.; Vijayan, D.S.
Abstract: The main aim of the present study is to comparatively evaluate Stress-Strain properties of Reinforced alkaline activated Metakaolin based Geopolymer concrete with Conventional concrete of M25 grade prepared with 3 and 4 numbers of hoop steel reinforcement. For studying Stress-Strain behavior under compression totally the 36 cylinders were tested out of which the 24 cylinders was prepared with Metakaolin based GPC and the remaining with conventional concrete M25 Grade. The flexible think was measured in this study is that the volumetric percentage of Reinforcement. The results exposed that confinement with hoop reinforcement significantly enhanced the strength of Metakaolin based GPC but not more than OPC and also it was found that the rate of stress increases when the percentage of the number of hoop reinforcement increased, similarly in case of strain it was decreased when the percentage of the number of hoop reinforcement increased. Hence it was concluded that the Metakaolin based GPC is not profitable that using instead of OPC along with any major form of reinforcement work.